Fenomena Dark Jokes di Kalangan Remaja : Telaah Hadis Tentang Etika Bercanda Perspektif Psikologis Kognitif - Nafa' Kamaliyah; Puteri Andini A.M.Y; Wafiq Azizah; Muhid (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The increasing prevalence of dark jokes among adolescents reflects a shift in their understanding of humor, particularly humor involving sensitive topics that may provoke diverse reactions. This study aims to examine the practice and reception of dark jokes among adolescents by reviewing the ethics of joking in hadith and analyzing it through a cognitive psychology perspective to understand the mental processes underlying adolescents’ evaluation of humor. This research employed a qualitative approach using a literature review of sources related to hadith on the etiquette of joking, humor theories, and fundamental concepts of cognitive psychology concerning adolescent perception and emotional responses. The findings indicate that dark jokes are commonly used by adolescents to lighten the atmosphere, strengthen peer relationships, or express psychological pressure, although they may also potentially offend or harm others. These practices are not fully aligned with the ethical principles of joking in the hadith, which emphasize mindfulness in speech and the avoidance of causing emotional harm. From a cognitive psychology perspective, this discrepancy can be attributed to adolescents’ still-developing cognitive abilities, particularly in considering the social impact of their statements. This study highlights the importance of humor literacy that integrates ethical awareness and an understanding of adolescent cognitive development, enabling humor to be used more wisely and responsibly within social interactions.